Clinical efficacy and learning curve of posterior percutaneous endoscopic cervical laminoforaminotomy for patients with cervical spondylotic radiculopathy. Issue 36 (9th September 2022) - Yao, Ran; Yan, Ming; Liang, Qingchen; Wang, Hongqing; Liu, Zuyao; Li, Fu; Zhang, Hao; Li, Ke; Sun, Fenglong
Abstract : In this study, we aimed to investigate the clinical efficacy and learning curve of posterior percutaneous endoscopic cervical laminoforaminotomy (PPECLF) in patients with cervical spondylotic radiculopathy (CSR). A total of 64 patients with CSR received PPECLF. Clinical outcome scores included the visual analog scale, Japanese Orthopedic Association score, neck disability index, and modified Macnab criteria. Radiological outcomes included the disc height, C2 to C7 Cobb angle, and range of motion. The learning curve was evaluated using cumulative sum analysis. Patients were divided into accumulation phase and mastery phase groups (A and B), and general data and surgical efficacy were compared between the 2 groups. Follow-up ranged from 12 to 24 months. Clinical outcome scores improved significantly at the final follow-up, and there were no differences in radiological outcomes. Surgical efficacy was excellent and good in 82.8% of patients. The operative time showed a decreasing trend with the accumulation of cases. Patients were divided and the 26th case was the cutoff point according to the learning curve. No significant differences were found in the clinical outcomes between the 2 groups. Decompression with PPECLF was safe and effective in the treatment of CSR. With the accumulation of cases, the operative time was gradually shortened, and the clinical efficacy was significant. The PPECLF procedure can be performed efficiently and safely to treat CSR.